PERENCANAAN DRAINASE GAYAMSARI SUBSISTEM KANAL BANJIR TIMUR SEMARANG - Rizki Ade Khoir; Novita Afrianti Panjaitan; Sri Eko Wahyuni; Hari Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Gayamsari District Area of Semarang is one of the flooded area. The causes of flooding is local rainfall that occurred in the village Gayamsari, Pandean Lamper, Siwalan and Sambirejo which is a sub-system of the East Flood Canal, where the channel capacity in the area can not accommodate the flow of water passing through the channel. Limited drainage capacity caused by the blockage of garbage and sediment that makes the water can not flow when it rains. This causes the drainage channel over capacity when it rains with great intensity and in a rather long time, which can result in a puddle with a depth of between 20-50 cm for ± 1-5 hours. To overcome this done drainage planning in order to cope with floods and inundation in the area. The initial steps of planning a drainage cover primary and secondary data collection, planning drainage used 14 years of rainfall data, topographic maps and the existing drainage system. In planning, hydrological analysis to seek the discharge plan with EPA SWMM program. Obtained flood discharge plan with a return period of 5 years on each subcatchment ranged from 0.24 to 3.81 m3 / sec. Furthermore, to determine the effectiveness of the existing channel cross section is modeled with HEC-RAS program. Planned cross-section with a steady flow conditions. The results of calculations using the program shows a cross section in the downstream Gajah Raya Street and Soekarno-Hatta Street can not accommodate discharge plan. Handling is done by increasing capacity of the drainage channel and making the detention basin.